Pelaksanaan Manajemen Kurikulum Pesantren Dalam Membentuk Karakter Mandiri Santri - Muhammad Yasin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Forming the independent character of students is not an easy job, where students who are accustomed to being in the cradle of their parents will tend to be spoiled and lazy when they have to face different realities in pesantren life, so good curriculum management is needed to grow their independent character. This study aims to analyze the implementation of Islamic boarding school curriculum management, and efforts to form the independent character of students in the Daarus Sholah Islamic boarding school, Kampung Kajang, South Sangatta. This research applies qualitative research with descriptive research type, where the data obtained is data collected in the form of descriptions, and illustrations. The result is that pesantren curriculum management cannot be separated from the management function known as POAC, namely planning, organizing, actuating, controlling, where the four functions were popularized with the terms planning, organizing, implementing, and evaluating. These four functions have been carried out at the Darus Sholah Very South Islamic boarding school. Furthermore, in an effort to form the independent character of students at the Daarus Sholah Islamic Boarding School, it is carried out with fish farming and agriculture programs as well as habituation of students in carrying out all their own activities of course accompanied by strict supervision from the boarding school caregivers. The implication is that this independent character is expected to be a provision for the students when the students are no longer in the boarding school environment and are no longer in the family environment when they are adults.